![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a.
$4(x+5)(x+6)(x+10)(x+12)=3x^2$
$4[(x+5)(x+12)][(x+6)(x+10)]=3x^2$
$4(x^2+17x+60)(x^2+16x+60)=3x^2$
Đặt $x^2+16x+60=a$ thì pt trở thành:
$4(a+x)a=3x^2$
$4a^2+4ax-3x^2=0$
$4a^2-2ax+6ax-3x^2=0$
$2a(2a-x)+3x(2a-x)=0$
$(2a-x)(2a+3x)=0$
Nếu $2a-x=0\Leftrightarrow 2(x^2+16x+60)-x=0$
$\Leftrightarrow 2x^2+31x+120=0\Rightarrow x=\frac{-15}{2}$ hoặc $x=-8$
Nếu $2a+3x=0\Leftrightarrow 2(x^2+16x+60)+3x=0$
$\Leftrightarrow 2x^2+35x+120=0\Rightarrow x=\frac{-35\pm \sqrt{265}}{4}$
b.
$(x+1)(x+2)(x+3)(x+6)=120x^2$
$[(x+1)(x+6)][(x+2)(x+3)]=120x^2$
$(x^2+7x+6)(x^2+5x+6)=120x^2$
Đặt $x^2+6=a$ thì pt trở thành:
$(a+7x)(a+5x)=120x^2$
$\Leftrightarrow a^2+12ax-85x^2=0$
$\Leftrightarrow a^2-5ax+17ax-85x^2=0$
$\Leftrightarrow a(a-5x)+17x(a-5x)=0$
$\Leftrightarrow (a-5x)(a+17x)=0$
Nếu $a-5x=0\Leftrightarrow x^2+6-5x=0$
$\Leftrightarrow (x-2)(x-3)=0\Rightarrow x=2$ hoặc $x=3$
Nếu $a+17x=0\Leftrightarrow x^2+17x+6=0$
$\Rightarrow x=\frac{-17\pm \sqrt{265}}{2}$
Vậy.........
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\text{a) }3x+6=8x+3\)
\(\Leftrightarrow3x-8x=3-6\)
\(\Leftrightarrow-5x=-3\)
\(\Leftrightarrow x=\frac{-3}{-5}=\frac{3}{5}\)
\(\text{Câu b và câu c bạn ghi rõ lại giùm}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 7x - 35 = 0
<=> 7x = 0 + 35
<=> 7x = 35
<=> x = 5
b) 4x - x - 18 = 0
<=> 3x - 18 = 0
<=> 3x = 0 + 18
<=> 3x = 18
<=> x = 5
c) x - 6 = 8 - x
<=> x - 6 + x = 8
<=> 2x - 6 = 8
<=> 2x = 8 + 6
<=> 2x = 14
<=> x = 7
d) 48 - 5x = 39 - 2x
<=> 48 - 5x + 2x = 39
<=> 48 - 3x = 39
<=> -3x = 39 - 48
<=> -3x = -9
<=> x = 3
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 8/x-8 + 11/x-11 = 9/x-9 + 10/ x-10
b, x/x-3 - x/x-5 = x/x-4 - x/x-6
c, 4/x^2-3x+2 - 3/2x^2-6x+1 +1 = 0
d, 1/x-1 + 2/ x-2 + 3/x-3 = 6/x-6
e, 2/2x+1 - 3/2x-1 = 4/4x^2-1
f, 2x/x+1 + 18/x^2+2x-3 = 2x-5 /x+3
g, 1/x-1 + 2x^2 -5/x^3 -1 = 4/ x^2 +x+1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{2}{x^2-x-6}+\dfrac{x+1}{x^2+x-12}=\dfrac{x}{x^2+6x+8}\)
\(\Leftrightarrow\dfrac{2}{\left(x-3\right)\left(x+2\right)}+\dfrac{x+1}{\left(x-3\right)\left(x+4\right)}=\dfrac{x}{\left(x+2\right)\left(x+4\right)}\)
=> 2(x+4)+(x+1)(x+2)=x(x-3)
⇔2x+8+x2+2x+x+2=x2-3x
⇔x2+5x+10=x2-3x
⇔x2-x2+5x+3x=-10
⇔8x=-10
\(\Leftrightarrow\dfrac{-5}{4}\)
Vậy S={-\(\dfrac{5}{4}\)}
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 3(x + 2) = 5x + 8
<=> 3x + 6 = 5x + 8
<=> 3x + 6 - 5x - 8 = 0
<=> -2x - 2 = 0
<=> -2x = 0 + 2
<=> -2x = 2
<=> x = -1
2) 2(x - 1) = 3(3 + x) + 3
<=> 2x - 2 = 9 + x + 3
<=> 2x - 2 = 12 + x
<=> 2x - 2 - 12 - x = 0
<=> x - 14 = 0
<=> x = 0 + 14
<=> x = 14
3) 5 - (x - 6) = 4(3 - 2x)
<=> 5 - x + 6 = 12 - 8x
<=> 11 - x = 12 - 8x
<=> 11 - x - 12 + 8x = 0
<=> -1 + 7x = 0
<=> 7x = 0 + 1
<=> 7x = 1
<=> x = 1/7
![](https://rs.olm.vn/images/avt/0.png?1311)